Spiritualty of Children in Families and Those in Residential Care - Kardum, Goran; Grčič, Ante; Marina, Marina (Revija za elementarno izobraževanje, 2025)
The aim of the study was to investigate the differences in the spirituality of children in residential care and children in families. Applying the method of pairs, children with behavioural problems who are users of residential care and children from families who are equal in terms of sociodemographic variables were selected for the sample. After applying a mixed methodology (Spiritual Sensitivity Scale and Santa Clara questionnaires, and Interpretive phenomenological analysis and thematic analysis of interviews), we obtained results indicating differences in the understanding of spirituality between these two groups. Children from residential care achieved higher results on spirituality questionnaires, and qualitative methodology determined a greater degree of compassion towards close people as well as a deeper relationship with the transcendent.
Keywords: spirituality, method of pairs, residential care, children, mixed methodology.